2019
DOI: 10.1186/s12935-019-0925-8
|View full text |Cite
|
Sign up to set email alerts
|

The diverse mechanisms and anticancer potential of naphthoquinones

Abstract: Cancer is one of the leading causes of death around the world and although the different clinical approaches have helped to increase survival rates, incidence is still high and so its mortality. Chemotherapy is the only approach which is systemic, reaching cancer cells in all body tissues and the search for new potent and selective drugs is still an attractive field within cancer research. Naphthoquinones, natural and synthetic, have garnered much attention in the scientific community due to their pharmacologi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
106
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 141 publications
(130 citation statements)
references
References 124 publications
2
106
0
1
Order By: Relevance
“…The 1,4-naphthoquinone pharmacophore has been at the center of numerous studies and has reported biological activity via a dianion species or radical anion [ 36 ]. Quinone moieties are present in several anticancer drugs including daunorubicin, doxorubicin and mitoxantrone [ 37 ] and many derivatives synthesized from 2-hydroxy-1,4-naphthoquinone have been demonstrated to have anticancer activity [ 38 ] resulting from redox cycling, arylation, intercalation, the induction of DNA strand breaks, the generation of free radicals and alkylation via quinone methide formation [ 38 ]. The anticancer activity of lawsone (1,4 naphthoquinone) has been attributed to its interaction with various signaling pathways via inducing the rapid formation of ROS which induces DNA damage and leads to cell death [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…The 1,4-naphthoquinone pharmacophore has been at the center of numerous studies and has reported biological activity via a dianion species or radical anion [ 36 ]. Quinone moieties are present in several anticancer drugs including daunorubicin, doxorubicin and mitoxantrone [ 37 ] and many derivatives synthesized from 2-hydroxy-1,4-naphthoquinone have been demonstrated to have anticancer activity [ 38 ] resulting from redox cycling, arylation, intercalation, the induction of DNA strand breaks, the generation of free radicals and alkylation via quinone methide formation [ 38 ]. The anticancer activity of lawsone (1,4 naphthoquinone) has been attributed to its interaction with various signaling pathways via inducing the rapid formation of ROS which induces DNA damage and leads to cell death [ 39 ].…”
Section: Introductionmentioning
confidence: 99%
“…Apoptosis, also known as active death process, is an active and gene-controlled process of cell death for maintaining the stability of the internal environment. At present, there are two main apoptotic signaling pathways, which are the intrinsic mitochondrial pathway and extrinsic death receptor pathway 21,22 . In the mitochondrial www.nature.com/scientificreports/ www.nature.com/scientificreports/ pathway of apoptosis, decrease in mitochondrial membrane potential promotes the release of Cytochrome c (Cyt c) from the mitochondria into the cytoplasm and activated caspase-3, caspase-7, and caspase-9.…”
Section: Resultsmentioning
confidence: 99%
“…The evaluation of the anticorrosive activity was performed by electrochemical tests using a 100 mL capacity eletrochemical cell of three electrodes: reference Hg/HgO (Analion), carbon counter (4.00 cm 2 ), and AISI 316 stainless steel as working electrode, with areas of 16.234 cm 2 , 17.768 cm 2 and 18.286 cm 2 . The stainless-steel surface were treated with 120, 400, and 600 sands.…”
Section: Evaluation Of the Corrosion Activitymentioning
confidence: 99%
“…For decades, these substances have been used for various purposes in different application areas, from biological and medicinal [1] [2] [3] [4] to materials science [5] [6] [7]. The 1,4-NQs are highly reactive building blocks in a large variety of chemical reactions, attracting many synthetic chemists inspired by the nature to produce technologically appealing and bioactive compounds [8] [9] [10].…”
Section: Introductionmentioning
confidence: 99%